As representações sociais de ambiente e qualidade de vida entre viticultores do município de Marialva - PR - Capelari, Silvia (2011)
The research aimed to study the social representations of environment and quality of life of small farmer families who grow vine in a rural community in Marialva - PR. Twelve families participated in the study, one man and one woman of each, totalizing twenty-four people. The question which guided this research was: Which are the social representations of environment and quality of life of these families, and how can these representations contribute to the reception of educational orientations which lead to a change in agricultural practices in the future? The study of social representations can offer a new comprehension on how these families think their practices in agriculture. This comprehension will enable the researcher to realize interventions based on the knowledge and actions of these families. The qualitative methodology counted on individual semi-structured interviews, drawing on the Theory of Social Representations of Serge Moscovici. The discourses were analyzed by using the rhetorical analysis. The results pointed that the social representations of environment and of quality of life are anchored in the need to survive. The nature is represented as a fundamental resource to life maintenance, and the representations of quality of life are related to economic aspects or as a means to keep human conditions of health, nourishment, etc. We concluded that the educational actions involving these farmers are very isolated and have not provided these families with a vision of the environment complexity which reflects on their quality of life. The subjects researched do not perceive themselves within the environment. The prospects of continuing this work point to the deployment of an environmental education program, involving farmers and their families, coordinated by the extension.